Phthalates toxicity in vivo to rats, mice, birds, and fish: A thematic scoping review - Mohammad Shah Alam; Zannatul Maowa; Mohammad Nazmol Hasan (Heliyon)
Background: Phthalates, a large group of endocrine disruptors, are ubiquitous in the environment and detrimental to human health. This scoping review aimed to summarize the effects of phthalates on laboratory animals relevant to humans, assess toxicity, and analyze mechanisms of toxicity for public health concerns. Methods: Articles were retrieved from Google Scholar, PubMed, ScienceDirect, and Web of Science search engines. The search used the term “toxicity of phthalates in vivo, animals or birds or fish.” Original research articles published between 2010 and 2024 describing in vivo toxicity in rat, mouse, bird, and fish models, were included. Conversely, articles that did not meet the above criteria were excluded from this scoping review. Two authors independently extracted data using data extraction tools based on themes, while a third arbitrated if consensus was not met. A senior researcher developed the themes, which were further refined through discussions. Data analysis involved quantitative (percentage of studies) and qualitative (content analysis) methods. Results: Of the 8180 articles screened, 153 met the inclusion criteria. Most of them were published after 2015 (74.50 %). The scoping review showed that DEHP (56.20 %) and DBP (21.57 %) were the most studied phthalates followed by BBP, DiBP, DMP, DEP, BBOP, and DiNP. Scarce data were available on DnOP, DPHP, DPeP, DUDP, DTDP, DMiP, and DiOP. Interestingly, studies of combinations of two or more phthalates were also present. The main laboratory animals employed were rats (48.37 %) and mice (39.87 %), while the least studied were birds (5.22 %) and fish (6.53 %). Most studies related to testicular toxicity (37.60 %), hepatotoxicity (23.53 %), and ovarian toxicity (18.30 %) investigations, while the rest consisted of neurotoxicity (6.88 %), renal toxicity (6.53 %), and thyroid toxicity studies (4.57 %). Studies focused on oxidative stress (34.64 %), apoptosis (22.22 %), steroid hormone deprivation (20.26 %), lipid metabolism disorder (11.76 %), and immunotoxicity (5.88 %) as mechanisms of toxicity. The most commonly used techniques were H&E, RT-qPCR, ROS assay, WB, IHC, ELISA, RIA, TUNEL, TEM, IFM, FCM, and RNA-seq. Conclusions: DEHP and DBP are the most toxic and studied phthalates, while BBP, DiNP, DiBP, DiDP, BBOP, DMP, and DiOP and their combinations require more accurate studies to confirm their toxic effects on human health and mechanisms of action. These will assist policymakers in adopting strategies to minimize public exposure and adverse effects.